Omental Cyst - Rare Cause of Abdominal Pain in a 7-Year-Old Child: A Case Report - Sayeed,Maimuna (2021)
Abstract: Introduction: Abdominal pain is a common complaint in children. In most cases it may be functional. Among all organic causes, an abdominal cyst of omental or mesenteric origin is an uncommon etiology. Case Presentation: A 7-year-old girl presented with a short history of abdominal pain for 1 month associated with gradual abdominal distention. Physical examination revealed a large oval palpable firm, non-tender mass extending almost the whole abdomen. Imaging studies were suggestive of an intra-abdominal cyst, and the diagnosis was confirmed after exploratory laparotomy. The patient was managed surgically by enucleation of the cyst. Conclusion: Omental cysts are a rare benign condition, but should be considered as a diagnostic hypothesis in children with abdominal pain with or without a mass. It is difficult to diagnose an omental/mesenteric cyst clinically. A proper imaging study can guide the diagnosis. After confirming the diagnosis, the main treatment would be surgical excision.